Efektivitas Dalethyne Modern Dressing pada Penyembuhan Luka pada Ulkus Kaki Diabetik: (Studi Kuasi-Eksperimental) - Dwi Yogo Budi Prabowo; Muhammad Anis Taslim; Madyo Adrianto (Pusat riset dan Inovasi Nasional, 2024)
Type 2 Diabetes Mellitus (DM) is characterized by hyperglycemia, which can lead to microangiopathic and macroangiopathic complications. One of the chronic complications is diabetic foot ulcer (DFU), which carries a high risk of infection and amputation. Preventing amputation can be achieved by accelerating wound healing. Dalethyne, a herbal product extracted through ozonization, contains essential oils, fatty acids, iodine, and peroxides. In wound care, Dalethyne acts as an antimicrobial agent that eliminates bacteria and promotes the formation of new tissue. This study aimed to examine the effect of modern Dalethyne dressings on wound healing among patients with diabetic foot ulcers. A quasi-experimental study with a non-equivalent control group pretest–posttest design was conducted at a wound care clinic in Semarang. Thirty participants with grade 2–3 diabetic foot ulcers were divided into an intervention group (Dalethyne dressing) and a control group (standard care). Wound healing was assessed using the DMIST scale before and after one week of treatment. Both groups showed improvement in DMIST scores post-treatment. However, the intervention group demonstrated significantly greater improvement (mean DMIST reduction of 48.50) compared to the control group (mean reduction of 16.50) (p = 0.001). Photographic evidence indicated more advanced granulation and epithelialization in the Dalethyne group. Modern wound care using Dalethyne effectively enhances wound healing in diabetic foot ulcers.